A lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit and its manufacturing method.
By using specific materials and modification techniques in the insulation and sheathing layer of multi-core cables, the flexibility and bending resistance of the cable are improved, and the problem of insufficient weight and bending resistance of existing cables when used in rail transit is solved, achieving more efficient cable performance.
Patent Information
- Application Number
- CN202411945634.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing multi-core cables are not flexible and bending resistant in rail transit, resulting in easy disconnection in complex application environments and being bulky and inconvenient.
The specific insulating layer and sheath layer material is designed. The insulating layer consists of 30-40 parts of linear low-density polyethylene, 8-20 polyacrylic acid modified pre-oxidized fibers, 2-5 parts of boron nitride nanosheets, etc. The sheath layer consists of 20-30 parts of polyvinyl chloride, 20-30 parts of maleic anhydride grafted polyvinyl chloride and other materials. The flexibility and bending resistance of the insulating layer and sheath layer are improved through technical means such as acrylic monomer modified pre-oxidized fibers and succinic anhydride modified lignocellulose.
It realizes the lightweight of multi-core cables, improves their flexibility and bending resistance when used in rail transit, reduces the risk of disconnection, and meets the lightweight requirements for cables in rail transit.
Smart Images

Figure CN119381056B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cables, and more specifically, to a lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit and a preparation method thereof. Background Art
[0002] Wires and cables are the main arteries and lifelines of rail transit. The usage of cables in rail transit construction is very large. Whether it is the transmission of electric energy or information, wires and cables are indispensable.
[0003] Rail transit cables include single-core power cables, multi-core control cables, data cables, sensor cables, jumper cables and many other types. Among them, the structure of ordinary multi-core cables is: a layer of insulation is extruded on several conductors to form a core wire, and several core wires form a bundle, and then a sheath layer is extruded on the outside. In order to ensure the insulation level of this multi-core cable, the thickness of its insulation layer and sheath layer is thicker, and the weight of the cable is heavier. In addition, if the control cable is used for the controlled object to be moved, it puts forward higher requirements on the flexibility and bending resistance of the control cable. For example, the invention patent CN201610278514.2 discloses a special elastomer insulated multi-core cable for rail transit vehicles, including a cable core, which is composed of a conductor and an inner insulating layer coated outside the conductor, the gap between the conductor and the inner insulating layer is filled with fireproof material, a thin layer is wrapped around the cable core, and the thin layer is coated with an inner shielding layer, and after adding a ground wire core, the outer shielding layer, outer insulating layer, and sheath are continuously wrapped in sequence, wherein the inner insulating layer and the outer insulating layer are both made of special elastomer insulating material. The softness and bending resistance of the prepared multi-core cable are not suitable for use in the small laying space of rail transit vehicles. Faced with the actual complex application environment, the general multi-core cable not only has poor bending resistance, but is also prone to wire breakage after repeated and torsion, and is relatively bulky to move. Summary of the invention
[0004] In order to solve the problems of poor flexibility and bending resistance of the above-mentioned existing multi-core cables, the present application provides a lightweight, highly flexible and bending-resistant multi-core data transmission cable for rail transit and a preparation method thereof.
[0005] In the first aspect, the present application provides a lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit, which adopts the following technical solution:
[0006] It comprises a cable core, an insulating layer and a sheath layer; wherein the cable core comprises a plurality of groups of twisted wire cores, each group of the twisted wire cores is formed by twisting two insulating single wires, each of the insulating single wires comprises a conductor and an insulating layer arranged in sequence from the inside to the outside, and the insulating layer is covered with a sheath layer;
[0007] The material of the insulating layer includes, by weight: 30-40 parts of linear low-density polyethylene, 8-20 parts of polyacrylic acid modified pre-oxidized fiber, 2-5 parts of boron nitride nanosheets, 1-2 parts of coupling agent, 10-15 parts of compatibilizer, 3-5 parts of cross-linking aid, and 0.5-1.5 parts of lubricant;
[0008] The materials of the sheath layer include, by weight: 20-30 parts of polyvinyl chloride, 20-30 parts of maleic anhydride grafted polyvinyl chloride, 10-15 parts of a compatibilizer, 13-16 parts of succinic anhydride modified lignin cellulose, 1-2 parts of a coupling agent, 2-6 parts of a lubricant, 0.5-2 parts of a high temperature resistant oxidant, and 5-10 parts of a cross-linking aid.
[0009] By adopting the above technical solution, the present application sequentially designs the raw materials of the insulation layer and the sheath layer to solve the problems of poor flexibility and bending resistance of existing multi-core cables. First, the insulation layer adopts pre-oxidized fiber, which has high strength and high modulus. The sheath layer adopts lignin cellulose, which has good toughness, dispersibility and chemical stability. While reducing the thickness of the insulation layer and the sheath layer, the weight of the cable is reduced, and the strength and tensile resistance of the multi-core cable are improved. It meets the lightweight requirements of rail transit multi-core cables.
[0010] The base of the insulation layer and the sheath layer is polyethylene and polyvinyl chloride. Although the strength of the multi-core cable is enhanced and the weight of the cable is reduced, the polyethylene and polyvinyl chloride materials are hard and brittle, which is not conducive to the performance improvement of the multi-core cable. After many experiments and studies, acrylic acid monomers and pre-oxidized fibers are added to the insulation layer material. During the polymerization of acrylic acid monomers, acrylic acid monomers react with oxygen-containing groups of pre-oxidized fibers. The pre-oxidized fibers are evenly dispersed in the insulation layer by utilizing the dispersion effect of acrylic acid monomer polymers. Acrylic acid improves the compatibility of polyethylene with other additives, and pre-oxidized fibers eliminate the bending stress of the material. The combination of the two greatly improves the flexibility and bending resistance of the insulation layer. Combined with boron nitride nanosheets, the sheet material eliminates the external force of the material from the horizontal and vertical directions, and the coupling agent, compatibilizer, and cross-linking agent improve the compatibility and film-forming properties between the materials.
[0011] Similarly, the sheath layer uses maleic anhydride grafted polyvinyl chloride; succinic anhydride modified lignin cellulose improves the brittleness of polyvinyl chloride. Acid anhydride modifiers improve the compatibility of polyvinyl chloride with other materials, and the modified cellulose improves the softness and bending resistance of the material. Succinic anhydride reacts with the hydroxyl groups of lignin cellulose to improve the dispersibility of lignin cellulose. Combined with coupling agents, compatibilizers, and cross-linking aids, the compatibility and film-forming properties of the various materials are improved.
[0012] Optionally, the thickness of the insulating layer is 0.2-0.3 mm.
[0013] By adopting the above technical solution, the present application uses acrylic monomer modified pre-oxidized fiber, which reduces the thickness of the insulation layer and reduces the weight of the cable. The thickness of the insulation layer is lower than that of most multi-core cables, meeting the lightweight requirements of rail transit cables.
[0014] Optionally, the thickness of the sheath layer is 0.4-0.6 mm.
[0015] By adopting the above technical scheme, the sheath layer adopts polyvinyl chloride grafted with maleic anhydride and lignin cellulose modified with succinic anhydride, which, on the one hand, improves the solubility of polyvinyl chloride, and on the other hand, reduces the weight of the sheath layer material and the thickness of the sheath layer, thereby reducing the weight of the cable. The thickness of the sheath layer is lower than that of most multi-core cables, meeting the lightweight requirements of rail transit cables.
[0016] Optionally, the pre-oxidized fiber has a diameter of 400-750 nm.
[0017] By adopting the above technical solution, when the pre-oxidized fiber is less than 400nm, the nano-scale fiber filaments are easy to agglomerate, and when mixed with the acrylic monomer solution, the solution viscosity increases and the modification effect is poor. When it is higher than 750nm, the pre-oxidized fiber is not easy to dissolve, which increases the brittleness of the insulation layer material.
[0018] Optionally, the aspect ratio of the boron nitride nanosheets is 800-1000.
[0019] By adopting the above technical solution, the present application adds boron nitride nanosheets to the insulating layer material, thereby improving the flexibility and bending resistance of the insulating layer. The sheet material eliminates the stress applied by external forces to the material in the lateral and longitudinal directions, and the flexibility of the material is increased when it is bent.
[0020] In a second aspect, the present application provides a method for preparing a lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit, which is characterized by comprising:
[0021] Step 1: Use a stranding machine to strand several wires into one strand at a pitch diameter ratio of 20-25 times, with the stranding direction being leftward, as a conductor;
[0022] Step 2: A layer of insulating layer material is uniformly extruded on the outside of the conductor by an extruder as an insulating single wire. Two insulating single wires are twisted into a group of twisted wire cores. Multiple groups of twisted wire cores form a cable core. A layer of sheath material is extruded outside the cable core by an extruder.
[0023] By adopting the above technical solution, a plurality of wires are firstly twisted into one strand by a stranding machine, and then a layer of the insulating layer material experimentally studied in this application is extruded by an extruder to form an insulating layer. Then, multiple groups of single wires are twisted to form a cable core, and a sheath layer is extruded on the outer layer of the cable core. The multi-core data transmission cable prepared by this application has light weight, high flexibility and bending resistance.
[0024] Optionally, the preparation method of the insulating layer material is: dissolving acrylic acid monomer in water, heating to 20-25° C., slowly adding pre-oxidized fiber under stirring, then adding initiator, stirring and reacting at 40-50° C. for 3 h, and drying at 60° C. to obtain black powder;
[0025] Boron nitride nanosheets, a coupling agent and a compatibilizer are mixed, and black powder, linear low-density polyethylene, a cross-linking aid and a lubricant are added in sequence and stirred evenly to obtain an insulating layer material.
[0026] By adopting the above technical scheme, acrylic acid monomer and pre-oxidized fiber undergo grafting reaction at 20-25°C. On the one hand, the modified pre-oxidized fiber improves its dispersibility in the polyethylene matrix. On the other hand, the grafted succinic anhydride is mixed with boron nitride nanosheets, coupling agent, and compatibilizer to improve the dispersibility of the boron nitride nanosheets. The prepared insulating layer improves the problems of poor softness and poor bendability in the prior art.
[0027] Optionally, the preparation method of the sheath layer material is: dissolving succinic anhydride in acetone to prepare a succinic anhydride acetone solution, adding an initiator, adding a lignin cellulose solution, reacting at room temperature for 24 hours, and drying to obtain succinic anhydride modified lignin cellulose;
[0028] The sheath layer material is obtained by uniformly mixing polyvinyl chloride, maleic anhydride grafted polyvinyl chloride, a compatibilizer, succinic anhydride modified lignin cellulose, a coupling agent, a lubricant, a high temperature resistant oxidant and a cross-linking auxiliary agent.
[0029] By adopting the above technical solution, the succinic anhydride-modified lignin cellulose improves the dispersibility of lignin cellulose in polyvinyl chloride. On the other hand, the combination of succinic anhydride-modified lignin cellulose and maleic anhydride-grafted polyvinyl chloride promotes the compatibility and processability of polyvinyl chloride with other additives. With the coordinated use of coupling agent, lubricant, high temperature resistant oxidant and cross-linking additive, the sheath layer material is not only light in weight, but also has improved softness and bending resistance.
[0030] Optionally, each of the wire bundles is drawn from a plurality of single wires, and the material of the single wires is aluminum alloy, soft round copper or tinned soft round copper.
[0031] By adopting the above technical solution, the conductor of the multi-core cable of the present application is made of tinned soft round copper, which has good conductivity, avoids oxidation, improves corrosion resistance, and saves costs.
[0032] In summary, this application has the following beneficial effects:
[0033] 1. The insulation layer uses pre-oxidized fiber, which has high strength and high modulus. The sheath layer uses lignin cellulose, which has good toughness, dispersibility and chemical stability. While reducing the thickness of the insulation layer and sheath layer, the weight of the cable is reduced, and the strength and tensile resistance of the multi-core cable are improved. It meets the lightweight requirements of rail transit multi-core cables;
[0034] 2. After many experiments and studies, acrylic acid monomers and pre-oxidized fibers are added to the insulating layer material. During the polymerization of acrylic acid monomers, acrylic acid monomers react with oxygen-containing groups of pre-oxidized fibers. The pre-oxidized fibers are evenly dispersed in the insulating layer by utilizing the dispersing effect of acrylic acid monomer polymers. Polyacrylic acid improves the compatibility of polyethylene with other additives, and pre-oxidized fibers eliminate the bending stress of the material. The combination of the two greatly improves the flexibility and bending resistance of the insulating layer.
[0035] 3. The sheath layer is made of maleic anhydride grafted polyvinyl chloride combined with succinic anhydride modified lignin cellulose to improve the brittleness of polyvinyl chloride. Succinic anhydride reacts with the hydroxyl groups of lignin cellulose to improve the dispersibility of lignin cellulose. The combination of coupling agent, compatibilizer and cross-linking aid improves the compatibility and film-forming properties of the materials. The modified lignin cellulose improves the softness and bending resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 These are the infrared spectra of pre-oxidized fibers and modified pre-oxidized fibers. DETAILED DESCRIPTION
[0037] The raw materials of the examples and comparative examples of the present application can be purchased commercially. The pre-oxidized fiber was purchased from Taizhou Keen Environmental Protection Technology Co., Ltd. with a gram weight of 250-500 g / m 2 , item number: MHT01, specifications are 50*50cm, thickness is 2-3mm.
[0038] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0039] Preparation Example 1
[0040] Preparation of insulating layer material: 15g acrylic acid monomer was dissolved in 200mL water, heated to 25°C, 5g pre-oxidized fiber was slowly added at a stirring speed of 300r / min, and then 0.01g benzoyl peroxide was added, stirred at 45°C for 3h, centrifuged at 5000r / min for 3min, and dried at 60°C for 12h to obtain 17g polyacrylic acid modified pre-oxidized fiber;
[0041] 4 g of boron nitride nanosheets, 1.5 g of A151 coupling agent, and 12 g of PE-g-MAH were mixed and stirred for 10 minutes, and then 17 g of polyacrylic acid modified pre-oxidized fiber, 35 g of linear low-density polyethylene, 4 g of DCP cross-linking agent, and 1 g of zinc stearate were added in sequence and mixed and stirred for 15 minutes to obtain an insulating layer material.
[0042] Preparation of sheath layer material: 8 g of succinic anhydride was dissolved in 50 mL of acetone to prepare a succinic anhydride acetone solution, and 0.08 g of diisopropylamine was added and stirred for 5 min. 5.5 g of lignin cellulose was added to 50 mL of acetone to prepare a lignin cellulose acetone solution. The succinic anhydride acetone solution and the lignin cellulose acetone solution were mixed, stirred at room temperature for 24 h, and dried at 60 ° C for 12 h to obtain 13 g of succinic anhydride modified lignin cellulose;
[0043] 25 g of polyvinyl chloride, 25 g of maleic anhydride grafted polyvinyl chloride, 12 g of PE-g-MAH compatibilizer, 13 g of succinic anhydride modified lignin cellulose, 1.5 g of A151 coupling agent, 4 g of zinc stearate, 1 g of Sumilizer GA-80, and 8 g of DCP crosslinking agent were mixed and stirred for 15 minutes to obtain a sheath layer material.
[0044] Preparation Example 2
[0045] Preparation of insulating layer material: 16 g of acrylic acid monomer was dissolved in 200 mL of water, heated to 20°C, 6 g of pre-oxidized fiber was slowly added at a stirring speed of 300 r / min, and then 0.01 g of benzoyl peroxide was added, stirred at 50°C for 3 h, centrifuged at 5000 r / min for 3 min, and dried at 60°C for 12 h to obtain 20 g of polyacrylic acid modified pre-oxidized fiber;
[0046] 5 g of boron nitride nanosheets, 2 g of A151 coupling agent, and 15 g of PE-g-MAH were mixed and stirred for 10 minutes, and then 20 g of polyacrylic acid modified pre-oxidized fiber, 40 g of linear low-density polyethylene, 5 g of DCP cross-linking agent, and 1.5 g of zinc stearate were added in sequence and mixed and stirred for 15 minutes to obtain an insulating layer material.
[0047] Preparation of sheath layer material: Dissolve 10g of succinic anhydride in 50mL of acetone to prepare a succinic anhydride acetone solution, add 0.08g of diisopropylamine and stir for 5min. Add 6g of lignin cellulose to 50mL of acetone to prepare a lignin cellulose acetone solution. Mix the above succinic anhydride acetone solution and the lignin cellulose acetone solution, stir and react at room temperature for 24h, and dry at 60℃ for 12h to obtain 16g of succinic anhydride modified lignin cellulose;
[0048] 30 g of polyvinyl chloride, 30 g of maleic anhydride grafted polyvinyl chloride, 15 g of PE-g-MAH compatibilizer, 16 g of succinic anhydride modified lignin cellulose, 2 g of A151 coupling agent, 6 g of zinc stearate, 2 g of Sumilizer GA-80, and 10 g of DCP crosslinking agent were mixed and stirred for 15 minutes to obtain a sheath layer material.
[0049] Preparation Example 3
[0050] Preparation of insulating layer material: 7 g of acrylic acid monomer was dissolved in 200 mL of water, heated to 23 ° C, and 3 g of pre-oxidized fiber was slowly added at a stirring speed of 300 r / min, and then 0.01 g of benzoyl peroxide was added, stirred at 40 ° C for 3 h, centrifuged at 5000 r / min for 3 min, and dried at 60 ° C for 12 h to obtain 8 g of polyacrylic acid modified pre-oxidized fiber;
[0051] 2 g of boron nitride nanosheets, 1 g of A151 coupling agent, and 10 g of PE-g-MAH were mixed and stirred for 10 min, and then 8 g of polyacrylic acid modified pre-oxidized fiber, 30 g of linear low-density polyethylene, 3 g of DCP cross-linking agent, and 0.5 g of zinc stearate were added in sequence and mixed and stirred for 15 min to obtain an insulating layer material.
[0052] Preparation of sheath layer material: Dissolve 7g of succinic anhydride in 50mL of acetone to prepare a succinic anhydride acetone solution, add 0.08g of diisopropylamine and stir for 5min. Add 5g of lignin cellulose to 50mL of acetone to prepare a lignin cellulose acetone solution. Mix the above succinic anhydride acetone solution and the lignin cellulose acetone solution, stir at room temperature for 24h, and dry at 60℃ for 12h to obtain 12g of succinic anhydride modified lignin cellulose;
[0053] 20 g of polyvinyl chloride, 20 g of maleic anhydride grafted polyvinyl chloride, 10 g of PE-g-MAH compatibilizer, 12 g of succinic anhydride modified lignin cellulose, 1 g of A151 coupling agent, 2 g of zinc stearate, 0.5 g of Sumilizer GA-80, and 5 g of DCP crosslinking agent were mixed and stirred for 15 minutes to obtain a sheath layer material.
[0054] Comparative Preparation Example 1
[0055] The difference from Preparation Example 1 is that the preparation method of the insulating layer material is different.
[0056] Preparation of insulating layer material: 4 g of boron nitride nanosheets, 1.5 g of A151 coupling agent, and 12 g of PE-g-MAH were mixed and stirred for 10 min, and then 15 g of polyacrylic acid, 5 g of pre-oxidized fiber, 35 g of linear low-density polyethylene, 4 g of DCP cross-linking agent, and 1 g of zinc stearate were added in sequence and mixed and stirred for 15 min to obtain the insulating layer material.
[0057] Comparative Preparation Example 2
[0058] The difference from Preparation Example 1 is that the preparation method of the sheath layer material is different.
[0059] Preparation of sheath layer material: 25g polyvinyl chloride, 25g maleic anhydride grafted polyvinyl chloride, 12g PE-g-MAH compatibilizer, 8g succinic anhydride, 5.5g lignin cellulose, 1.5g A151 coupling agent, 4g zinc stearate, 1g Sumilizer GA-80, and 8g DCP cross-linking agent were mixed and stirred for 15 minutes to obtain the sheath layer material.
[0060] Comparative Preparation Example 3
[0061] The difference from Preparation Example 1 is that the sheath layer material does not include maleic anhydride grafted polyvinyl chloride.
[0062] Preparation of sheath layer material: 8 g of succinic anhydride was dissolved in 50 mL of acetone to prepare a succinic anhydride acetone solution, and 0.08 g of diisopropylamine was added and stirred for 5 min. 5.5 g of lignin cellulose was added to 50 mL of acetone to prepare a lignin cellulose acetone solution. The succinic anhydride acetone solution and the lignin cellulose acetone solution were mixed, stirred at room temperature for 24 h, and dried at 60 ° C for 12 h to obtain 13 g of succinic anhydride modified lignin cellulose;
[0063] 25 g of polyvinyl chloride, 25 g of maleic anhydride grafted polyvinyl chloride, 12 g of PE-g-MAH compatibilizer, 13 g of succinic anhydride modified lignin cellulose, 1.5 g of A151 coupling agent, 4 g of zinc stearate, 1 g of Sumilizer GA-80, and 8 g of DCP crosslinking agent were mixed and stirred for 15 minutes to obtain a sheath layer material.
[0064] Example 1
[0065] A method for preparing a lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit, comprising the following steps:
[0066] Step 1: Use a stranding machine to twist several wire bundles into one wire at a pitch diameter ratio of 20-25 times, and the twisting direction is left, wherein each of the wire bundles is drawn from several single wires, and the material of the single wire is tinned soft copper with a purity of more than 99.99% as a conductor.
[0067] Step 2: Use an extruder to evenly extrude a layer of insulating layer material on the outside of the conductor as an insulating single wire, wherein the insulating layer material is prepared using Preparation Example 1. The thinnest point of the insulating layer is ≥ 80% of the nominal thickness of the insulation, the concentricity of the insulating layer is ≥ 75%, and the thickness of the insulating layer is 0.2mm. Two insulating single wires are twisted at a pitch diameter ratio of 12-16 times to form a group of twisted wire cores, and the twisting direction is to the left. Multiple groups of twisted wire cores form a cable core, and a layer of sheath layer material is extruded on the outer layer of the cable core using an extruder, and the sheath layer material is prepared using Preparation Example 1. The thickness of the sheath layer is 0.4mm.
[0068] Example 2
[0069] Step 1: Use a stranding machine to strand several wire bundles into one wire at a pitch diameter ratio of 20-25 times, and the stranding direction is left, wherein each of the wire bundles is drawn from several single wires, and the material of the single wires is aluminum alloy as a conductor.
[0070] Step 2: Use an extruder to evenly extrude a layer of insulating layer material on the outside of the conductor as an insulating single wire, wherein the insulating layer material is prepared using Preparation Example 2. The thinnest point of the insulating layer is ≥ 80% of the nominal thickness of the insulation, the concentricity of the insulating layer is ≥ 75%, and the thickness of the insulating layer is 0.3mm. Two insulating single wires are twisted at a pitch diameter ratio of 12-16 times to form a group of twisted wire cores, and the twisting direction is to the left. Multiple groups of twisted wire cores form a cable core, and a layer of sheath layer material is extruded on the outer layer of the cable core using an extruder, and the sheath layer material is prepared using Preparation Example 2. The thickness of the sheath layer is 0.5mm.
[0071] Example 3
[0072] Step 1: Use a stranding machine to strand several wire bundles into one wire at a pitch diameter ratio of 20-25 times, and the stranding direction is left. Each of the wire bundles is drawn from several single wires, and the material of the single wire is soft round copper with a purity of more than 99.99% as a conductor.
[0073] Step 2: Use an extruder to evenly extrude a layer of insulating layer material on the outside of the conductor as an insulating single wire, wherein the insulating layer material is prepared using Preparation Example 3. The thinnest point of the insulating layer is ≥ 80% of the nominal thickness of the insulation, the concentricity of the insulating layer is ≥ 75%, and the thickness of the insulating layer is 0.2mm. Two insulating single wires are twisted at a pitch diameter ratio of 12-16 times to form a group of twisted wire cores, and the twisting direction is to the left. Multiple groups of twisted wire cores form a cable core, and a layer of sheath layer material is extruded on the outer layer of the cable core using an extruder, and the sheath layer material is prepared using Preparation Example 3. The thickness of the sheath layer is 0.4mm.
[0074] Comparative Example 1
[0075] The difference from Example 1 is that the insulating layer material is prepared using Comparative Preparation Example 1.
[0076] Comparative Example 2
[0077] The difference from Example 1 is that the sheath layer material is prepared using Comparative Preparation Example 2.
[0078] Comparative Example 3
[0079] The difference from Example 1 is that the sheath layer material is prepared using Comparative Preparation Example 3.
[0080] Performance testing
[0081] Detection Methods
[0082] Bending resistance test: The conductors of the multi-core data transmission cables of Examples 1-3 and Comparative Examples 1-3 are continuously bent at a bending diameter of 150 mm to determine the maximum number of bending times that the conductors can withstand without breaking the circuit.
[0083] Wear test: Referring to the records in GJB 1916-1994 and JB / T 10696.6-2007, the maximum number of wear times of the cable prepared in the present application without electrical contact is measured.
[0084] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-3
[0085]
[0086] Combining the data of Examples 1, 2, and 3, it can be seen that the difference between Examples 1, 2, and 3 is only the different raw material composition ratios. The bending resistance and softness of Example 1 are higher than those of Examples 1 and 2, proving that the raw material ratio of Example 3 is the best.
[0087] Combining the data of Example 1 and Comparative Example 1, it can be seen that the difference between Example 1 and Comparative Example 1 is that in Comparative Example 1, polyacrylic acid and pre-oxidized fiber are simply blended without modification. The bending resistance and softness of the multi-core data transmission cable prepared in Example 1 are greater than those in Comparative Example 1, and the tensile strength and elongation at break are higher than those in Comparative Example 1. It is proved that simply adding pre-oxidized fiber and then mixing it with other components cannot meet the performance requirements of multi-core cables. The pre-oxidized fiber is modified by polyacrylic acid to improve the dispersibility of the pre-oxidized fiber. Polyacrylic acid improves the compatibility of polyethylene with other additives. The pre-oxidized fiber eliminates the bending stress of the material. The combination of the two greatly improves the flexibility and bending resistance of the insulation layer.
[0088] Figure 1The infrared spectra of pre-oxidized fiber and modified pre-oxidized fiber are shown in Figure 2. -1 is the stretching vibration peak of the hydroxyl group of the pre-oxidized fiber, 2937 cm -1 、1452cm -1 The absorption peaks corresponding to the CH stretching vibration and CH in-plane bending vibration of pre-oxidized fibers are 1748 cm -1 The C=O stretching vibration absorption peak of the pre-oxidized fiber is at 1412 cm -1 、2936cm -1 and 2847cm -1 The bending and stretching vibrations of CH2 on the polyacrylic acid molecular chain are not observed in the infrared spectrum of the modified pre-oxidized fiber. -1 The C=O peak of polyacrylic acid modified pre-oxidized fiber moved to 1551 cm -1 . It was proved that polyacrylic acid reacted chemically with the pre-oxidized fibers.
[0089] Combining the data of Example 1 and Comparative Example 2, it can be seen that the difference between Example 1 and Comparative Example 2 is that Comparative Example 2 simply blends succinic anhydride and lignin cellulose without modification. The bending resistance and softness of the multi-core data transmission cable prepared in Example 1 are greater than those of Comparative Example 2, and the tensile strength and elongation at break are higher than those of Comparative Example 2. It is proved that the present application uses succinic anhydride-modified lignin cellulose to improve the bending resistance and softness of the sheath layer material. In addition, succinic anhydride and maleic anhydride improve the compatibility of polyvinyl chloride with other materials, improve the dispersibility of lignin cellulose, and combine with coupling agent, compatibilizer, and cross-linking aid to improve the compatibility and film-forming properties between the materials.
[0090] Combining the data of Example 1 and Comparative Example 3, it can be seen that the difference between Example 1 and Comparative Example 3 is that the sheath layer material of Comparative Example 3 does not include maleic anhydride grafted polyvinyl chloride. The bending resistance and softness of the multi-core data transmission cable prepared in Example 1 are greater than those of Comparative Example 3, and the tensile strength and elongation at break are higher than those of Comparative Example 3. It is proved that maleic anhydride grafted polyvinyl chloride improves the compatibility of polyvinyl chloride with other materials and improves the processing and forming properties of the sheath layer material.
[0091] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit, characterized in that: It comprises a cable core, an insulating layer and a sheath layer; wherein the cable core comprises a plurality of groups of twisted wire cores, each group of the twisted wire cores is formed by twisting two insulating single wires, each of the insulating single wires comprises a conductor and an insulating layer arranged in sequence from the inside to the outside, and the insulating layer is covered with a sheath layer; The material of the insulating layer includes, by weight: 30-40 parts of linear low-density polyethylene, 8-20 parts of polyacrylic acid modified pre-oxidized fiber, 2-5 parts of boron nitride nanosheets, 1-2 parts of coupling agent, 10-15 parts of compatibilizer, 3-5 parts of cross-linking aid, and 0.5-1.5 parts of lubricant; The materials of the sheath layer include, by weight: 20-30 parts of polyvinyl chloride, 20-30 parts of maleic anhydride grafted polyvinyl chloride, 10-15 parts of a compatibilizer, 13-16 parts of succinic anhydride modified lignin cellulose, 1-2 parts of a coupling agent, 2-6 parts of a lubricant, 0.5-2 parts of a high temperature resistant oxidant, and 5-10 parts of a cross-linking aid.
2. A lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit according to claim 1, characterized in that: The thickness of the insulating layer is 0.2-0.3 mm.
3. A lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit according to claim 1, characterized in that: The thickness of the sheath layer is 0.4-0.6 mm.
4. A lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit according to claim 1, characterized in that: The diameter of the pre-oxidized fiber is 400-750 nm.
5. The lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit according to claim 1, characterized in that: The aspect ratio of the boron nitride nanosheets is 800-1000.
6. The method for preparing a lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit according to claim 1, characterized in that: include: Step 1: Use a stranding machine to strand several wires into one strand at a pitch diameter ratio of 20-25 times, with the stranding direction being leftward, as a conductor; Step 2: Use an extruder to evenly extrude a layer of insulating material on the outside of the conductor as an insulating single wire, twist two insulating single wires into a group of twisted wire cores, and multiple groups of twisted wire cores form a cable core. Use an extruder to fill a layer of sheath material on the outer layer of the cable core to obtain a multi-core data transmission cable.
7. The method for preparing a lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit according to claim 6, characterized in that: The preparation method of the insulating layer material is as follows: dissolving acrylic acid monomer in water, heating to 20-25° C., slowly adding pre-oxidized fiber under stirring, then adding initiator, stirring and reacting at 40-50° C. for 3 hours, and drying at 60° C. to obtain black powder; Boron nitride nanosheets, a coupling agent and a compatibilizer are mixed, and black powder, linear low-density polyethylene, a cross-linking aid and a lubricant are added in sequence and stirred evenly to obtain an insulating layer material.
8. The method for preparing a lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit according to claim 6, characterized in that: The preparation method of the sheath layer material is as follows: dissolving succinic anhydride in acetone to prepare a succinic anhydride acetone solution, adding an initiator, adding a lignin cellulose solution, reacting at room temperature for 24 hours, and drying to obtain succinic anhydride modified lignin cellulose; The sheath layer material is obtained by uniformly mixing polyvinyl chloride, maleic anhydride grafted polyvinyl chloride, a compatibilizer, succinic anhydride modified lignin cellulose, a coupling agent, a lubricant, a high temperature resistant oxidant and a cross-linking auxiliary agent.
9. The method for preparing a lightweight, highly flexible, and bend-resistant multi-core data transmission cable for rail transit according to claim 6, characterized in that: Each of the wire bundles is drawn from a plurality of single wires, and the material of the single wires is aluminum alloy, soft round copper or tinned soft round copper.
Citation Information
Patent Citations
Special elastomer insulated multi-core cable for track transportation vehicle
CN105860260A
Silicone rubber sheath and cable prepared by applying same
CN111334048A
Biomass-based modified epoxy resin and production process thereof
CN114591494A